2016
DOI: 10.1124/jpet.116.234096
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor Activation Attenuates Inflammation-Associated Intestinal Epithelial Barrier Dysfunction by Inhibiting Cytokine-Induced Myosin Light-Chain Kinase Expression and c-Jun N-Terminal Kinase 1/2 Activation

Abstract: The inflammatory bowel diseases (IBDs) are chronic inflammatory disorders with a complex etiology. IBD is thought to arise in genetically susceptible individuals in the context of aberrant interactions with the intestinal microbiota and other environmental risk factors. Recently, the pregnane X receptor (PXR) was identified as a sensor for microbial metabolites, whose activation can regulate the intestinal epithelial barrier. Mutations in NR1I2, the gene that encodes the PXR, have been linked to IBD, and in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 72 publications
0
51
1
Order By: Relevance
“…To our knowledge, this is the first report implicating the CAR in the regulation of intestinal epithelial wound healing and mucosal restitution following inflammation‐associated injury. We, and others, have reported that the PXR, a closely related receptor, plays an important role in gastrointestinal tract, regulating barrier function, inflammatory signalling and mucosal repair following injury (Shah et al, ; Cheng et al, ; Terc et al, ; Venkatesh et al, ; Garg et al, ). These studies and others, in conjunction with the data presented herein, suggest that xenobiotic receptors play a key role in the maintenance of intestinal mucosal homeostasis, and that their dysfunction may contribute to the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To our knowledge, this is the first report implicating the CAR in the regulation of intestinal epithelial wound healing and mucosal restitution following inflammation‐associated injury. We, and others, have reported that the PXR, a closely related receptor, plays an important role in gastrointestinal tract, regulating barrier function, inflammatory signalling and mucosal repair following injury (Shah et al, ; Cheng et al, ; Terc et al, ; Venkatesh et al, ; Garg et al, ). These studies and others, in conjunction with the data presented herein, suggest that xenobiotic receptors play a key role in the maintenance of intestinal mucosal homeostasis, and that their dysfunction may contribute to the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that xenobiotic receptors are key regulators of intestinal mucosal homeostasis, based on their ability to modulate the function of the intestinal epithelium and resident mucosal immune cell populations (Qiu et al, ; Venkatesh et al, ; Ji et al, ; Chng et al, ; Garg et al, ). We have previously reported that the PXR, a receptor closely related to the CAR, enhances intestinal epithelial wound healing and protects the mucosal barrier during inflammatory stress (Terc et al, ; Garg et al, ). Furthermore, others have characterized the anti‐colitic effects of PXR signalling (Shah et al, ; Cheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nr1i2 −/− mice exhibit impaired epithelial barrier function, and administration of synthetic NR1I2 agonists exerts protective effects in mouse models of colitis (Dou et al, 2013; Garg et al, 2016; Shah et al, 2007; Terc et al, 2014; Venkatesh et al, 2014). Interestingly, the combined knockout of Nr1i2 and the gene encoding the LPS sensor toll-like receptor 4 ( Tlr4 ) can rescue the phenotype of Nr1i2 −/− mice, possibly because it counteracts the accelerated cell death of inflammatory monocytes observed in NR1I2-deficient mice (Z.…”
Section: Microbiome-associated Metabolites That Shape the Immune Systemmentioning
confidence: 99%
“…The PXR is highly expressed in the liver and intestine where it can regulate nuclear factor Îș‐light‐chain‐enhancer of B cells (NFÎșB) activation and the expression of a number of inflammatory mediators . Importantly, PXR signaling in the intestine can dampen TLR4 signaling to promote intestinal barrier function and prevent inflammation in the GI tract . The influence of the PXR in the modulation of enteric infections has also emerged with evidence for the involvement of a PXR‐TLR4–driven mechanism .…”
Section: Introductionmentioning
confidence: 99%